Trends in the pattern of discarding in the hake (Merluccius hubbsi and Merluccius australis) fishery in the SW Atlantic. - Bellido-Millán, José María; Portela, Julio; Wang, Jianjun; Pierce, Graham John (2012)
This paper presents results from the EC Study Project 99/016 “Data collection for stock assessment of two hakes (Merluccius hubbsi and M. australis) in international and Falkland waters of the SW Atlantic”. Historical fishery and biological data series available from IEO (1988 onwards) were used to describe and quantify patterns and spatio-temporal changes in catches and discards in the hake fishery. Data were collected by scientific observers on board Spanish fishing vessels operating in the study area. Data collected on fishing activity included effort, catches and discards of target and non-target species on a haul-by-haul basis. Biological information (size, sex, maturity, etc) on target species was recorded on a daily basis, while biological data on non-target species was recorded periodically. The “discards ratio” was calculated by each haul, defined as the total weight of fish discarded divided by the total catch weight. The most important by-catch species are hoki or whiptailed hake (Macruronus magellanicus), red cod (Salilota australis), southern blue whiting (Micromesistius australis), Patagonian toothfish (Dissostichus eleginoides) and kingclip (Genypterus blacodes). Discards included both target and non-target species. The most commonly discarded species were Patagonotothen spp. (almost 100% of the catch is discarded), whiptailed hake (Macruronus magellanicus) (25% discarded), southern blue whiting (12%) and red cod (6%). These percentages vary with area, year and fishing season. The four target species (Merluccius hubbsi, Merluccius australis, Illex argentinus and Loligo gahi) have discard ratios below 5%. In recent years discard ratios for all species except Patagonotothen spp. have fallen below 15%.